Augmented Reality Technology in Human Anatomy As a Strategy to Improve Student Achievement - Kusmawati, Wiwik; Zaini, Moh.; Kurniawan, Rubbi; Saputro, Yulianto Dwi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
Learning Human Anatomy uses human skeleton props in the form of human mankind. The props turned out to be ineffective because carrying them was difficult due to their relatively large size. Augmented Reality will make it easier to recognize the human body in a virtual three-dimensional, and real-time manner.The results of this study aim to determine the increase in student achievement in Human Anatomy with Augmented Reality. The research method is a quasi-experimental method. Sampling technique with simple random sampling. The samples are class C class 2021 students as the experimental class and class D class 2021 students as the control class. Data collection techniques using tests and non-tests. The instrument is an objective test of the multiple choice type, and the non-test instrument is a questionnaire. The data obtained were analyzed using the prerequisite test for normality and homogeneity tests. The results of the t-test that was carried out with the SPSS program, it was found that the tcount value was greater than the ttable value, meaning that there was a significant difference in student achievement in the experimental class and the control class. It could be concluded that there were differences in student achievement in Human Anatomy with Augmented reality. Augmented Reality can be used to improve student achievement in Human Anatomy.